The Effect of Gamma Irradiation as a Phytosanitary Treatment on Physicochemical and Sensory Properties of Bartlett Pears. Issue 9 (11th September 2013) - Abolhassani, Yalda; Caporaso, Fred; Rakovski, Cyril; Prakash, Anuradha
Abstract: A major concern in exporting agricultural commodities is the introduction or spread of exotic quarantine pests to the new area. To prevent spread of insect pests, various phytosanitary measures are used. Worldwide commercial use of irradiation as a phytosanitary treatment has increased greatly in recent years; however, trade has been limited to tropical fruits. Bartlett pear is a major summer variety of California pears with great potential and market for export. In this study, the effect of gamma irradiation at dose levels of 400, 600, and 800 Gy on physicochemical properties and sensory attributes of early and late harvest Bartlett pears was investigated. Firmness and color changes indicate that irradiation delayed the ripening of pears by 1 d. For the early harvest pears, scarring, bruising, and off flavor were significantly increased at the highest irradiation dose (800 Gy). The appearance of early harvest 800 Gy irradiated pears was the only attribute that received significantly ( P ≤ 0.05) lower scores than the control in consumer testing. For the late harvest pears, the 400 Gy fruit had lowest levels of scarring and bruising as rated by trained panelist but consumers did not score the control and 800 Gy fruit differently for any attribute. Titratable acidity, total soluble solids, and chroma were significantly ( P ≤ 0.05) decreased and hue increased by irradiation for the early harvest pears. These results suggest that there was a difference in radiotolerance of early and late harvest pears, but in both cases, irradiation at 400 to 600 Gy seemed to maintain best quality.